Cue Consistency Matters: How and When Newcomers Respond to Supervisor Creativity Expectations - Chen, J; Cooper-Thomas, HD; Cheung, G (Informa UK Limited, 2023)
Organizations may hire newcomers as a source of creativity, bringing fresh ideas and novel solutions to benefit organizational performance. However, the conditions that foster newcomer innovation are not well understood. Drawing on behavioral plasticity and cue consistency theories, we investigate the combined influence of new job self-efficacy and two work design factors (work autonomy and work demands) affecting how supervisor creativity expectations (SCEs) translate into newcomers behaving innovatively. Two-wave data were collected from 108 graduates of a university in China. Results using reliability-corrected single indicator latent moderated structural equation modeling (RCSLMS) supported our hypotheses. Thus, SCEs predicted newcomer innovative behavior more strongly for newcomers with low new job self-efficacy. Moreover, supporting cue consistency theory, newcomers who perceived high SCEs and low new job self-efficacy demonstrated the highest level of innovative behavior when work autonomy was high or work demands were low. These results broaden the application of behavioral plasticity theory for understanding newcomer behaviors. Further, our findings emphasize the importance of consistent work environment cues to encourage newcomer innovation.
Keywords: 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Behavioral and Social Science; 1503 Business and Management; 1505 Marketing; 1605 Policy and Administration; Industrial Relations; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; 5201 Applied and developmental psychology